Potential use of Fourier transform infrared spectroscopy for differentiation of bovine and porcine gelatins - Hashim, DM; Man, YBC; Norakasha, R; Shuhaimi, M; Salmah, Y; Syahariza, ZA (Elsevier Sci Ltd, 2024)
Indexed by SCOPUS/WOS